Numerical Study of a Gas Turbine Engine Ground Vortex - Barata, Jorge M M (2012)
A computational method was used to predict and understand ground vortices forming between the ground and a 1/1th scale model intake of a engine. Calculations have been performed for the case of an irrotational crossflow mode of formation. Two different kinds of vortices appear around the intake: an inlet vortex and a trailing vortex. The computational method was found to describe all the main features of the flow for full scale geometry.